Move like everyone is watching: Social context affects head motion and gaze in string quartet performance. Issue 4 (8th August 2021) - Bishop, Laura; González Sánchez, Victor; Laeng, Bruno; Jensenius, Alexander Refsum; Høffding, Simon
Abstract : Ensemble musicians engage with each other visually through glances and body motion. We conducted a case study to test how string quartet musicians would respond to playing conditions that were meant to discourage or promote visually communicative behaviour. A quartet performed in different seating configurations under rehearsal and concert conditions. Quantity of head motion was reduced when musicians' gaze was constrained. Differences in gaze and body motion between musicians reflected their musical roles in the ensemble. Overall, our findings suggest that gaze and motion dynamics vary within and between performances in response to changing musical, situational and social factors.